Measuring respiratory symptoms in moderate/severe asthma: evaluation of a respiratory symptom tool, the E-RS®: COPD in asthma populations - Maggie Tabberer; Robyn von Maltzahn; Elizabeth D. Bacci; Hayley Karn; Ray Hsieh; Timothy A. Howell; Zelie Bailes; Andrew Fowler; Laurie Lee; Lindsey T. Murray (SpringerOpen, 2021)
Abstract Background Symptom constructs included in the Evaluating Respiratory Symptoms in Chronic Obstructive Pulmonary Disease (E-RS®: COPD) tool may be relevant to patients with asthma. The purpose of this study was to evaluate content validity and psychometric performance of the E-RS: COPD in moderate/severe asthma patients. Methods Content validity of the E-RS: COPD was evaluated in patients with moderate/severe asthma using concept elicitation and cognitive debriefing interviews. Secondary analyses using data from two clinical trials in patients with moderate/severe asthma evaluated the factor structure of the E-RS: COPD plus two supplementary items (wheeze; shortness of breath with strenuous physical activity) and assessed psychometric properties of the tool, which will be referred to as E-RS®: Asthma when used in asthma populations. Results Qualitative interviews (N = 25) achieved concept saturation for asthma respiratory symptoms. Concepts in the E-RS: COPD were relevant to patients and instructions were understood. Most patients (19/25; 76%) reported experiencing all concepts in the E-RS: COPD; no patients indicated missing symptoms. Secondary analyses of clinical trial data supported the original factor structure (RS-Total and three symptom-specific subscales). The two supplemental items did not fit with this factor structure and were not retained. RS-Total and subscale score reliability was high (internal consistency [α] > 0.70). Validity was demonstrated through significant (P < 0.0001) relationships with the St George's Respiratory Questionnaire (SGRQ) and Asthma Symptom Severity scale. E-RS: Asthma was responsive to change when evaluated using SGRQ, Patient Global Impression of Change and Asthma Quality of Life Questionnaire as anchors (P < 0.0001). Clinically meaningful change thresholds were also identified (RS-Total: − 2.0 units). Conclusions The E-RS: Asthma is reliable and responsive for evaluating respiratory symptoms in patients with moderate/severe asthma.